Pengembangan Aplikasi 5S Management System - Sartikha; Noper Ardi; Kholifatussiddiq (Politeknik Caltex Riau, 2022)
5S is a framework methodology derived from the Japanese language, namely seiri (整理), seiton (整頓), seisō(清掃), seiketsu (清潔), and shitsuke (躾). In practice, the party who will report every problem andviolation is the auditor and the department that processes and follows up on every report received from theauditor is the facility. Until now, there are still many obstacles faced in running 5S. The development of thisapplication aims to facilitate the management of PT Galaksi Investasi Harapan in managing problems andviolations that occur against 5S in the work environment of PT Galaksi Investasi Harapan. To support thissystem, several features have also been added to calculate the time in carrying out problem solving actions sothat problems can be resolved on time. In addition, in solving problems for the approval of the president director,there is also a function for the approval of the president director so that every problem reported in the 5SManagement System is also known by the president director of PT Galaksi Investasi Harapan.